Cytogenetic and molecular risk-driven conditioning intensity in acute myeloid leukemia patients undergoing stem cell transplantation with post-transplant cyclophosphamide: a study from the acute leukemia working party of the EBMT - Sanz, Jaime; Labopin, Myriam; Versluis, Jurjen; Blaise, Didier; Lazzari, Lorenzo; Montoro, Juan; Van Gorkom, Gwendolyn; von dem Borne, Peter; Sandrine, Loron; Rovira, Montserrat; Reményi, Péter; Chevallier, Patrice; et al. (Bone marrow transplantation, 2025)
We retrospectively analyzed the impact of conditioning intensity on transplant outcomes according to their cytogenetic/molecular risk in a cohort of 1823 patients with acute myeloid leukemia (AML) and intermediate- or adverse-risk cytogenetics in first complete remission (CR1). These patients received their first hematopoietic stem cell transplantation (HSCT) using post-transplant cyclophosphamide (PTCy). The intermediate-risk cytogenetic group included 1386 (76%) patients, and 608 (34%) had mutated FLT3-ITD. Myeloablative conditioning was used in 930 patients (51%), while 1130 (62%) received an intensified conditioning (score ≥2.5) based on the transplant conditioning intensity (TCI) score. Conditioning intensity using the myeloablative/reduced intensity stratification did not impact transplant outcomes across the entire cohort. However, a higher TCI score was associated with a lower risk of relapse, with no effect on survival. In specific cytogenetic risk groups, a higher TCI score did not influence outcomes in the adverse-risk group. In the intermediate-risk group, the impact varied with FLT3-ITD status. Patients with FLT3-ITD mutation who received a higher TCI showed a beneficial effect on relapse, leukemia-free survival (LFS), and overall survival. Conversely, in FLT3-ITD wild-type patients, more intense conditioning had a detrimental effect on graft-versus-host disease-free, and relapse-free survival with no effect on other outcomes. In conclusion, for AML patients in CR1 undergoing HSCT with PTCy, it is crucial to consider cytogenetic risk and molecular status when selecting the conditioning regimen. Intensive conditioning should be considered for patients with intermediate-risk cytogenetics and mutated FLT3-ITD but should probably be avoided for those with wild-type FLT3-ITD.
Keywords: Young Adult; Hematopoietic Stem Cell Transplantation; Male; retrospektivní studie; Risk Factors; mladý dospělý; Cyclophosphamide; Adolescent; Adult; transplantace hematopoetických kmenových buněk; akutní myeloidní leukemie; Aged; dospělí; mužské pohlaví; senioři; příprava pacienta k transplantaci; mladiství; Transplantation Conditioning; lidé; ženské pohlaví; Humans; cyklofosfamid; rizikové faktory; Retrospective Studies; Female; lidé středního věku; Leukemia, Myeloid, Acute; Middle Aged